Mesoligia furuncula Denis & Schiffermuller 1775 - Dubatolov, V. V.; Zinchenko, V. K; Ustjuzhanin, P. Ya. (Zenodo, 2023)
Mesoligia furuncula ([Denis et Schiffermüller], 1775) MATERIAL. Russia : Kunashir Island, Yuzhno-Kurilsk, Nature Reserve “Kurilsky” administration territory, dry specimens at window, 13.IX 2022, 2 ♂. DISTRIBUTION. A widely distributed transpalearctic species; in the Pacific region it is known from Sakhalin and Japan: Hokkaido, Honshu (Shikata, 2011). Published as part of Dubatolov, V. V., Zinchenko, V. K & Ustjuzhanin, P. Ya., 2023, Autumn moths and butterflies (Lepidoptera) new for the fauna of Kunashir Island, pp. 11-24 in Far Eastern Entomologist 474 on page 18, DOI:10.25221/fee.474.3, http://zenodo.org/record/7945971